BUKU BAHASA ARAB MADRASAH IBTIDAIYAH (MI) DI PEKALONGAN - Moch. Lukluil Maknun (JURNAL PENELITIAN, 2014)
This is qualitative research that aims to describe the suitability of teaching Arabic books (class I and IV) in MI using KTSP curriculum with Content and Competency Standards set government policy, and a description of the book to teach Arabic MI is needed to cope with the new curriculum in 2013. The method used is a qualitative method, using content analysis of BSNP (National Education Standards Agency) and needs analysis. Suitability of the Arabic book by SK KD government set on average for class I applied sufficiently and still need to be further improved. As for class IV, SK KD can be applied with good and balanced, but to listening competencies, especially in the identification of letters hijaiyah not get enough servings. There are two possible models that can be created for teach book in the coming school year, the first is a thematic integrative book of PAI MI according to the new curriculum in 2013, or second is a Arabic books MI generally for the new school year.